Enrique San Román (1945-2019) - Aramendia, Pedro Francisco (2020)
An homage to the Argentinian Photochemist Enrique San Román is presented. Enrique led the Photochemistry and Chemical Kinetics research group in the Department of Inorganic, Analytical and Physical Chemistry in the Faculty of Exact and Natural Sciences of the University of Buenos Aires from 1984 until his death in July 2019. He left a strong legacy in Chemical Kinetics and Photochemistry in Argentina. He is remembered as a meticulous and very knowledgeable scientist and teacher, a loyal friend and a generous and integer human being.